An experimental research on medium: the use of banana sap as an alternative medium for artworks / Hisammudin Ahmad - Ahmad, Hisammudin (2007)
The use of banana sap, as a medium for artwork has never been explored in Malaysia.Banana sap is used in other countries such as Indonesia as textile dying, Philippine used as raw materials to produced ink for printer and Latin America as medicinal uses. Banana sap from some parts of the tree contain pigment and dyes, thus not aware of this potential medium is a waste.This materials is biodegradable and research was conducted especially to test the potential of banana sap as a pigment and dye to be used as a medium in creating artwork.